Effect of Corruption on Health Service Delivery in Magwi County-Eastern Equatoria State, Republic of South Sudan - Ben, Otto Joseph; Sendawula, Noah (Advances in Social Sciences Research Journal, 2023)
The study examined the effect of corruption on service delivery in local governments, a case study of health service delivery in Magwi County-Eastern Equatoria State of South Sudan. Specifically, study examined the level of corruption in health service delivery Magwi County-Eastern Equatoria State of South Sudan; assessed the quality of health service delivery in Magwi County-Eastern Equatoria State of South Sudan; and established the effect of corruption on health service delivery in Magwi County-Eastern Equatoria State of South Sudan. The study used descriptive research design. The study population was 75 where a sample of 63 respondents was selected using simple random and purposive sampling techniques. The study used both self-administered questionnaire and interview guide. Findings revealed that, it is a common practice in public facilities to first cash in individual healthcare providers to receive treatment, money intended for healthcare services is embezzled, there is high rates of favoritism where family members, relatives and friends receive the treatment first before others, people pay bribes to receive treatment in public health facilities, and healthcare providers sell public drugs to individual drug shops. It is concluded that corruption is the reason why public investment in health coupled with high rates of private spending has not translated into good health outcomes. The study recommends an establishment of an independent system to supervise delivery of services as this will help reduce corrupt tendencies. Furthermore, GoSS should develop a political will to fight and reduce corruption in Local government and all sphere of public institutions.